Upaya Meningkatkan Kemampuan Menyelesaikan Soal Matematika melalui Penerapan Model Direct Instruction pada Siswa Kelas II MI Esa Nusa Islamic School Kabupaten Tangerang - Novia Putri ; Mawardi Mawardi; Een Unaenah; Novia Putri Yuliani (Departement of Mathematics Education, 2023)
This research is Clash Action Research (CAR) which aims to improve ability to solve math problems through the application of the Direct Instruction model to class II MI Esa Nusa Islamic School students. This research was conducted in two research cycles. Data collection in this study was carried out using participant observation and written tests. Based on the results of the study, it was concluded that the use of the Direct Instruction model could improve students' ability to solve math problems. This is supported by the existence of research data which shows an increase in the percentage of completeness of the written test conducted at the second meeting in each cycle. During the pre-cycle, the students' completeness was only 52.17%, after the implementation of the first cycle with the Direct Instruction learning model, the completeness of students' math problems was 65.21%, then in cycle II, the completeness of the ability to work on math problems reached 91.30%.The use of the Direct Instruction learning model can improve indicators of the learning ability of class II B students at MI Esa Nusa Islamic School Tangerang Regency in 2021/2022. The average evaluation of student learning outcomes after implementing CAR with the Direct Instruction learning model was originally 65.22 to 75.65 in Cycle I and 89.13 in Cycle II.